PENDIDIKAN MULTIKULTURAL UNTUK ANAK USIA DINI: PERSPEKTIF ISLAM - Handayani, Dita; Ruswandi, Uus; Hadiana, M. Eri (FASTABIQ: JURNAL STUDI ISLAM, 2022)
Multicultural education in early childhood is very important because it is an alternative solution to the rise of human crimes with many racial, cultural and religious backgrounds. Theology lessons in schools tend to be taught simply to strengthen faith and its attainment to heaven without being accompanied by awareness of dialogue with other religions. This condition makes religious education very exclusive and intolerant. So it is very important to teach multicultural education to early childhood. The research method, is library research. The study approach uses analytical descriptive of thoughts or figure views who discuss multicultural themes. The Research objectives is to find the important role of multicultural education at the early childhood education level for the future development of society. The results of the research show that multicultural education is increasingly urgent to be given to early childhood in schools because with multicultural education, schools become a field for teaching tolerance, and at the same time training and building the character of students so that they are able to act democratically, humanely and pluralistically.Keywords: Early Childhood, Multicultural education, Islam